Effect of Inverter Frequency on Electric Motor-Driven Air Conditioning Systems Repurposed from Combustion Engine Cars for Electric Vehicle Applications - Kenny, Jonathan; Yusivar, Feri (International Journal of Electrical, Computer, and Biomedical Engineering, 2024)
This research introduces a framework for the adaptation of conventional automotive air conditioning systems in electric vehicle conversions by modifying them to operate with an electric motor driven by an inverter, aimed at reducing waste and promoting energy efficiency. The experiment was conducted on an AC system from a combustion engine car, tested independently to evaluate the effects of varying inverter frequencies on cooling performance and power consumption. Data were collected using multiple blower fan speeds, with additional alternator integration tested to maintain system efficiency. The results highlight optimal settings for minimizing energy consumption while achieving effective cooling, providing valuable insights for sustainable EV conversions.